Penerapan Pembelajaran dengan Pendekatan Open Ended terhadap Kemampuan Pemecahan Masalah Matematika di SMK Negeri 1 Sukaluyu Cianjur (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims: 1) To determine whether or not there is an influence of the Open Ended Approach on solving mathematical problems of class X APHP students of SMK Negeri 1 Sukaluyu Cianjur, 2) To determine the increase in mathematical problem solving abilities of class X APHP students of SMK Negeri 1 Sukaluyu Cianjur, 3) To determine the effect of the open ended learning approach on mathematical problem solving abilities. The research method used is quasi experimental. The sampling used is Purposive Sampling. The target population in this study were all students at SMK Negeri 1 Sukaluyu Cianjur who were registered in the even semester of the 2024/2025 academic year consisting of 2 classes. The results of the study showed that the open ended learning approach can present more interesting mathematics learning and students become more active in participating. During the study, the researcher observed the learning process. When students are taught using the open ended learning approach, students become more interested in learning to solve mathematical problems.